Mini Review: Structure and Function of Nematode Phosphorylcholine-Containing Glycoconjugates - Buitrago, Geraldine; Duncombe-Moore, Josephine; Harnett, Margaret M.; Harnett, William (Frontiers in Tropical Diseases, 2021)
An unusual aspect of the biology of nematodes is the covalent attachment of phosphorylcholine (PC) to carbohydrate in glycoconjugates. Investigation of the structure of these molecules by ever-increasingly sophisticated analytical procedures has revealed that PC is generally in phosphodiester linkage with C6 of N-acetylglucosamine (GlcNAc) in both N-type glycans and glycosphingolipids. Up to five PC groups have been detected in the former, being located on both antenna and core GlcNAc. The PC donor for transfer to carbohydrate appears to be phosphatidylcholine but the enzyme responsible for transfer remains to be identified. Work primarily involving the PC-containing Acanthocheilonema viteae secreted product ES-62, has shown that the PC attached to nematode N-glycans possesses a range of immunomodulatory properties, subverting for example, pro-inflammatory signalling in various immune system cell-types including lymphocytes, mast cells, dendritic cells and macrophages. This has led to the generation of PC-based ES-62 small molecule analogues (SMAs), which mirror the parent molecule in preventing the initiation or progression of disease in mouse models of a number of human conditions associated with aberrant inflammatory responses. These include rheumatoid arthritis, systemic lupus erythematosus and lung and skin allergy such that the SMAs are considered to have widespread therapeutic potential.